Genetics and Age-Related Eye Disease Study Formulation Interaction in Neovascular Age-Related Macular Degeneration. (January 2021) - Kaufman, Stephen R.; Yoganathan, Pradeepa; Small, Kent W.; Rusia, Deepam; Pachydaki, Sophia I.; Conti, Stephen M.; Wenz, Robert E.; Gersman, Mark A.; Shaya, Fadi S.; Kustra, Rafal
Purpose: This work aims to determine whether previously defined genotype risk groups interact with Age-Related Eye Disease Study formulation (AREDS-F) use in progression to neovascular age-related macular degeneration (nvAMD). Methods: We conducted a case-only study of 265 nvAMD patients. Patients were anonymously genotyped at the complement factor H and age-related maculopathy susceptibility 2 loci and segregated into genotype groups (GTGs) defined by specific combinations of risk alleles. Physicians, who were blind to patients' GTGs, obtained patients' AREDS-F use history. The facility performing genetic analysis was blind to the AREDS-F use history. We used logistic analysis to estimate the interaction coefficient between AREDS-F use and GTG 2 vs GTG 3 in a general-population model. Results: The odds ratio of numbers of patients reporting prior AREDS-F use to nonuse for GTG 2 vs GTG 3 was 4.18 ( P = .001). Logistic regression, correcting for nongenetic risk factors, gave an estimate of the β for interaction of AREDS-F with genotype of 1.57 ( P = .001). This estimates a corrected odds ratio associated with the effect of interaction of 4.81 between those in GTG 2 compared with those in GTG 3. Conclusions: Our data indicate an interaction between GTGs and AREDS-F use that is consistent in size and direction with previously published reports, which had found that using AREDS-F supplements significantly increases the risk of nvAMD for some users and significantly protects other users.